Micro-PIXE analysis of doped SiO2 fibres intended as TL dosimeters for radiation measurements - Abdul Sani, S.F.; Grime, G.W.; Palitsin, V.; Mahdiraji, G.A.; Abdul Rashid, H.A.; Maah, M.J.; Bradley, D.A. (John Wiley & Sons, 2015)
Sample elemental concentrations can be determined using the microbeam proton-induced X-ray emission (PIXE) technique, providing non-destructive simultaneous low-background multi-element analysis. Present interest concerns analysis of Ge-doped SiO2 fibres intended as high spatial-resolution thermoluminescence (TL) dosimeters for radiation measurements in place of their more typical applications in telecommunications. During fibres fabrication, defined amounts of the Ge dopant are added, the dopant more usually having a determining role in the transmission properties of the fibre. Characteristic X-rays produced in PIXE analysis provide information on the relative distribution of elements within a sample, as in for instance Ge and Si concentrations, the Ge acting as point defect centres that promote TL. With the dopant tending to diffuse in and away from the fibre core, it is essential to define the sample matrix composition in order to accurately evaluate the X-ray yield. This is determined in part using simultaneous Rutherford Back Scattering analysis. In present work, PIXE/Rutherford Back Scattering measurements have been employed to ascertain dopant concentrations of fibres that have been fabricated at the University of Malaya with a view to improving TL yield. Present results concern cylindrical fibres, nominally with 4, 6 and 8 weight peak Ge concentrations and flat fibres of nominal 6 weight Ge concentration. For the cylindrical fibres, Ge dopant concentration has been found to be in the range of 2.41-4.56, 6.44-8.29 and 10.27-12.25 weight, respectively, while for the flat fibres, the Ge concentration range is broader, at 0.07-6.55 weight. Copyright (c) 2014 John Wiley & Sons, Ltd.